1998
DOI: 10.2307/2446640
|View full text |Cite
|
Sign up to set email alerts
|

The tortoise and the hare: choosing between noncoding plastome and nuclear Adh sequences for phylogeny reconstruction in a recently diverged plant group

Abstract: Phylogenetic resolution is often low within groups of recently diverged taxa due to a paucity of phylogenetically informative characters. We tested the relative utility of seven noncoding cpDNA regions and a pair of homoeologous nuclear genes for resolving recent divergences, using tetraploid cottons (Gossypium) as a model system. The five tetraploid species of Gossypium are a monophyletic assemblage derived from an allopolyploidization event that probably occurred within the last 0.5-2 million years. Previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
319
3
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(345 citation statements)
references
References 100 publications
21
319
3
2
Order By: Relevance
“…Phylogenies of the Hawaiian mints have been reconstructed from datasets composed of commonly used DNA sequence markers, including cpDNA and nuclear ribosomal 5S non-transcribed spacer and external transcribed spacer regions (Lindqvist and Albert, 2002;Roy et al, 2013), which are rapidly evolving in many other species (Baldwin and Markos, 1998;Shaw et al, 2005;Small et al, 1998), but they fail to resolve relationships among the Hawaiian mints. A similar pattern of low genetic diversity has been noted in other recent radiations of Hawaiian plants (Appelhans et al, 2014;Baldwin and Sanderson, 1998;Cronk et al, 2005;Givnish et al, 2009;Givnish et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenies of the Hawaiian mints have been reconstructed from datasets composed of commonly used DNA sequence markers, including cpDNA and nuclear ribosomal 5S non-transcribed spacer and external transcribed spacer regions (Lindqvist and Albert, 2002;Roy et al, 2013), which are rapidly evolving in many other species (Baldwin and Markos, 1998;Shaw et al, 2005;Small et al, 1998), but they fail to resolve relationships among the Hawaiian mints. A similar pattern of low genetic diversity has been noted in other recent radiations of Hawaiian plants (Appelhans et al, 2014;Baldwin and Sanderson, 1998;Cronk et al, 2005;Givnish et al, 2009;Givnish et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To better resolve the evolutionary pattern of floral structures in Lepidium, a phylogenetic study using a single-copy nuclear gene was required, because such markers better reflect biparental lineages of homoploid and allopolyploid hybrids and thus are powerful tools in reconstructing reticulate histories of plant groups (16)(17)(18).…”
mentioning
confidence: 99%
“…Resequencing of hundreds of orthologous loci that broadly sample the genomes of diploid cottons sheds light on the types and rates of evolutionary mechanisms operating in the B7 million years (Small et al, 1998;Cronn et al, 2002) since divergence of these species from common ancestors. Different DNA sequence fragments ranged widely in levels of polymorphism.…”
Section: Levels and Patterns Of Divergence Of Dna Sequencesmentioning
confidence: 99%
“…Prior studies used only small numbers of nucleotides either from chloroplast (Wendel and Albert, 1992;Small et al, 1998) or nuclear DNA (Seelanan et al, 1997;Small et al, 1999;Cronn et al, 2002;Wendel and Cronn, 2003). Early studies using cpDNA (Wendel and Albert, 1992;Small et al, 1998) suggested the C genome to have diverged first from the common ancestor shared by both A and D genome species. However, later research using genomic DNA suggested D genome species to have diverged first (Cronn et al, 2002;Wendel and Cronn, 2003).…”
Section: Reassessing the Relationships Among Diploid Cottonsmentioning
confidence: 99%